ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PRESTASI BELAJAR MATA DIKLAT PRODUKTIF SISWA PROGRAM KEAHLIAN AKUNTANSI PADA SMK NEGERI 3 SURAKARTA TAHUN DIKLAT 2007-2008 - Listyani, Erythrina; Siswandari, Siswandari (MIIPS, 2008)
The objective of this research is to find out any factors which influence the learning achievement of productive subject of skill accounting program student at SMK Negeri 3 Surakarta, school year 2007-2008.The method has been used in this research is quantitative descriptive. The population is 237 student of grade X, XI, and XII of skill accounting program student SMK Negeri 3 Surakarta, school year 2007-2008. The technique sampling is Cluster Random Sampling, 113 student.Â  The collecting data technique which has been used is observation, questionnaire, interview and documentation. Based on the data analysis and the discussion, it can be concluded that there are nine factors which influence the learning achievement of productive subject of skill accounting program student. That is (1) relationship factor, (2) self-potential and learning factor, (3) fatigue factor, (4) family factor, (5) student learning condition factor, (6) learning facility factor, (7) physical and psychological factor, (8) willingness factor, and (9) economical factor. Based on the data analysis and discussion, it also can be concluded that all variables which group becoming six factors hypnotized in this research is accepted as new factor which influence the learning achievement of productive subject of skill accounting program student although social factor, in fact, doesnât influence the learning achievement of productive subject of skill accounting program student.Â